Identification of Clostridium septicum in a tubo-ovarian abscess: A rare case and review of the literature - Yavuzcan Ali; Çağlar Mete; Dilbaz Serdar; Kumru Selahattin; Avcıoğlu Fatma; Üstün Yusuf (Vojnosanitetski Pregled, 2014)
Introduction. Tubo-ovarian abscess (TOA) is a conglomerated mass of pelvic organs including tube, ovary, and bowel. The most commonly isolated organisms from TOAs are Escherichia coli (E. coli) and Bacteroides species. Case Report. We reported a case of Clostridium septicum (C. septicum) infection from a ruptured TOA with atypical clinical features. Culture of intra-abdominal free fluid obtained during surgery yielded C. septicum. VITEK II (bioMérieux, France) automated system was used for advanced identification of the bacteria. Parenteral clindamycin in combination with an aminoglycoside was used. The patient was discharged 19 days after the surgery and was clinically asymptomatic 6 months after the surgery. Conclusion. The differential diagnosis of TOA caused by C. septicum can be difficult, due to the lack of the symptoms. Tissues infected with C. septicum can become necrotic. A combination of early, adequate antibiotic therapy and surgery is the key point of the treatment.